The neuroprotective effects of novel estrogen receptor GPER1 in mouse retinal ganglion cell degeneration. (December 2019) - Jiang, Mengnan; Ma, Xueyun; Zhao, Qingqing; Li, Ying; Xing, Yiqiao; Deng, Qinqin; Shen, Yin
Abstract: Purpose: To investigate the potential protective effect of novel G protein coupled estrogen receptor (GPER1) against the neurotoxicity induced by NMDA in the mouse retina. Methods: We induce retinal ganglion cells (RGCs) toxic injury through intravitreal injection of NMDA or acute ocular hypertension (AOH) induced by anterior chamber infusion with saline. Endogenous ligand 17-β-estradiol (E2), GPER1 agonist (G-1), and E2 with GPER1 antagonist (G-15) or classic estrogen receptor α and β (ERα and ERβ) antagonist tamoxifen (TAM) were subcutaneous administered before NMDA to identify the possible involved receptors. Immunofluorescence staining was performed to explore the survival of RGCs and Müller cell gliosis. TUNEL staining was used to evaluate the RGC apoptosis. The involved molecular pathway was detected via antibody array expression profiling. Results: Activation of estrogen receptor by E2 or G-1 could significantly rescue the RGCs injury in NMDA administration. The protective effect was carried exclusively by GPER1 activation. E2 application can still mimicked the protective function when estrogen receptor α and β (ERα and ERβ) blocked by tamoxifen (TAM), while the effects was blocked by GPER1 antagonist G-15. Moreover, the TUNEL positive RGCs and GFAP expression level were both attenuated in G-1 application and the effects could be reversed by G-15. In addition, application of the PI3K/Akt antagonist LY294002 counteracted the effect of G-1. And a number of apoptosis regulatory factors decreased dramatically in the G-1 group, including Bad, Caspase 3, Caspase 7, Smad2, P-53 and TAK1. Also, similar protective effect of G-1 was spotted in acute ocular hypertension (AOH) model. Conclusion: Estrogen played a protective role via a novel estrogen receptor, GPER1, instead of classical receptors ERα or ERβ. Activation of GPER1 attenuated RGCs apoptosis and Müller cells gliosis, indicating GPER1 as a potential treatment target in RGCs degeneration diseases. Highlights: The novel estrogen receptor GPER1 expressed in the inner retina. Activation of GPER1 showed protective effects of RGCs in NMDA induced injury. PI3K/Akt pathway was involved in the regulatory network of GPER1. GPER1 activation also showed protective effects in acute ocular hypertension.